Positive Parenting Training for Increasing Self-Acceptance of Parents with Special Need Children in Sorong City - Syalviana, Evie; Syahrul, Syahrul (PT. Riset Press International, 2024)
Having a healthy and perfect child is every parent's dream. There are times when the expectations are not the same as the reality when children are born with developmental barriers. This fact illustrates that the process of parents in accepting children with special needs is not easy. Especially in the Sorong city. There is not therapy and treatment spaces in Sorong City. Thus making the stress level and lower parental self-acceptance. Therefore, the purpose of this research is to analize whether positive parenting training can increase the self-acceptance of parents with special need children in Sorong city. The research method used is an experimental pretest-posttest control group design. The data collection method used the provision of a self-acceptance scale at the time of the pretest and posttest, observation and interviews during the training. Before the training was carried out, the researchers first made a training module along with the pretest and posttest. The results showed that the level of parental acceptance ranged from 6 to 10 Of the 38 participants who participated in the training optimally. So it can be concluded that positive parenting training can increase the self-acceptance of parents with special need children in sorong city